ANALISIS USAHA BUDIDAYA IKAN LELE SANGKURIANG (Clarias gariepinus) DI PUSAT PELATIHAN PERTANIAN PEDESAAN SWADAYA (P4S) LAU KAWAR SAMBOJA KECAMATAN SAMBOJA KABUPATEN KUTAI KARTANEGARA - Trisna Handayani; Said Abdussyahid; Eko Sugiharto (2339-1324, 2021)
The purpose of this research is to know the analysis of the business of the cultivation of catfish sangkuriang (Clarias gariepinus) and know the stages in the cultivation of catfish sangkuriang (Clariasgariepinus). The sample methodusedis a case study method that focuses only on one respondent, Mr. Jumanan tarigan as the owner and founder of the Agricultural and Rural Training Center (P4S) Lau Kawar samboja. The data analysis methods used are qualitative descriptiveanalysis methods, business analysis and marketingchannels. The results of this study show that the cultivation of catfish sangkuriang (Clarias gariepinus) has the potential to develop in the future. The potential of cultivation and marketing is seen from the high survival of sangkurinag catfish (Clarias gariepinus) and the high interest in buying people. Keywords : Analysis, Cultivation of Sangkuriang Catfish